Methodical Approach to Assessing the Regional Economic Security Level Based on its Components Systemic Interrelations - Onischenko, Svitlana; Bondarevska, Olha; ., . (International Journal of Engineering and Technology, 2018)
At the present stage of development of Ukraine, the differences in the regions competitiveness levels due to the destabilizing factors influence are aggravated, which is a danger both for the state economy as a whole and for its regions. Therefore, the need for timely and comprehensive assessment of the territorial systems economic security, detailed study of the factors influencing regional economic security level and the interrelations between its functional components arise.The purpose of the study is to assess regional economic security level and investigate the systemic interrelations of its components on the basis of a retrospective analysis.The integral assessment of regional economic security level is suggested based on the combined use of indicative and functional methods. It has been determined that the most indicators deviate from threshold values due to a number of destabilizing and disincentive powerful factors influence.It has been established that demographic and investment components have instant dependence and the greatest influence on regional economic security unsatisfactory state. For each safety component, two indicators that most affect its integral assessment are highlighted.The study of the economic security components systemic interrelations enables local governments to apply effective measures to counter real threats and neutralize them when forming strategic and program documents on ensuring regional development security.Â Â